HUBUNGAN ANTARA INDEKS MASSA TUBUH DENGAN RISIKO SARKOPENIA PADA LANJUT USIA DI KELURAHAN UNTIA KOTA MAKASSAR - Sarira, Christine Milenia; Aras, Djohan; Ita Rini (Indonesian Journal of Physiotherapy, 2023)
Objective: To determine the relationship between body mass index and the risk of sarcopenia in the elderly in Untia Village, Makassar City. Methods: This research is a quantitative study with a cross-sectional research design. The sample was selected using a purposive sampling method and 67 samples were obtained that met the criteria. Body Mass Index (BMI) is calculated based on the formula of body weight divided by the square of height in meters, while the risk of sarcopenia is known using calf circumference as an indicator of muscle mass. Results: In this study, BMI in the normal category dominated (62.7%), followed by obese elderly (14.9%), obese (10.4%), thin (7.5%), and very thin (4.5%). Furthermore, it was obtained that the elderly had low muscle mass as much as 76.1% which referred to the condition of the risk of sarcopenia. The correlation test used was the Pearson product moment and the results obtained were a p value of 0.000 (p <0.05) which means there is a relationship between body mass index and risk sarcopenia in the elderly in Untia Village, Makassar City. The correlation coefficient value is positive at 0.486 with a medium/moderate relationship level. Conclusion: There is a significant relationship between body mass index and the risk of sarcopenia in the elderly in Untia Village, Makassar City. Keywords: Aging; Body Massa Indeks (BMI); Elderly; Geriatric; Physiotherapy; Sarcopenia